2002
DOI: 10.2337/diacare.25.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Hormones and the Development of Type 2 Diabetes in Older Men and Women: the Rancho Bernardo Study

Abstract: OBJECTIVE -To determine the prospective association between endogenous sex hormones and the development of type 2 diabetes in older men and women.RESEARCH DESIGN AND METHODS -A standardized medical history was obtained, an oral glucose tolerance test was performed, and plasma samples for sex hormones and covariates were collected from ambulatory, community-dwelling men and women at baseline from 1984 to 1987 . Approximately 8 years later (1992, another medical history was obtained, an oral glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
398
7
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 530 publications
(446 citation statements)
references
References 47 publications
28
398
7
13
Order By: Relevance
“…Therefore, central obesity-a hallmark of metabolic syndrome [20]-and degree of androgen deficiency was suspected to be closely related in patients with hypopituitarism. These results were similar to those in normal aging males [21,22], and patients with diabetes [23,24]. Unlike other studies [2,4,25], our studied patients with hypopituitarism had lower HOMA-IR than the healthy control group (HOMA-IR, 2.22 ± 0.22 vs.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, central obesity-a hallmark of metabolic syndrome [20]-and degree of androgen deficiency was suspected to be closely related in patients with hypopituitarism. These results were similar to those in normal aging males [21,22], and patients with diabetes [23,24]. Unlike other studies [2,4,25], our studied patients with hypopituitarism had lower HOMA-IR than the healthy control group (HOMA-IR, 2.22 ± 0.22 vs.…”
Section: Discussionsupporting
confidence: 89%
“…Although caution should be exerted in the interpretation of nonsignificant results, our data suggested that in aging men with predefined low normal bioavailable testosterone levels, insulin sensitivity did not change during testosterone treatment. Indeed, observational studies supported a link between low testosterone and insulin resistance, i.e., low testosterone predisposed to the metabolic syndrome and type 2 diabetes in older men (Oh et al 2002). Such studies have emphasized the need for interventional studies to clarify cause and effect.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between insulin and androgens has been recognized for some time, as men with low testosterone are prone to decreased lipolysis of the central abdominal fat, an adverse metabolic profile, insulin resistance, hyperinsulinemia and type II diabetes. [46][47][48] Alternatively, insulin is also associated with a decrease in hepatic sex hormone-binding globulin production, 49 perhaps increasing the levels of unbound and biologically available testosterone. However, it is possible that pituitary luteinizing hormone release also may decline subsequently through a feedback loop to lower testosterone synthesis and restore the balance between free and bound testosterone levels.…”
Section: Discussionmentioning
confidence: 99%